Quality Indicators of Cotton Fiber in the Care of " Ravnaq-1 " Goose in the Range of 76 Sm - Salomov Shavkat Turobovich, Teshayev Fatullo Jurakulovich, Achilov Sanjar Geldiyarovich, Mukhammadov Yuldoshbek Akmalo’g’li (International Journal of Modern Agriculture, 2021)
In our scientific research, observations were made by using a simple method between 60 sm and 76 sm lines in a simple and milling cultivator. Bunda soil porosity was observed in the analysis with an increase of 76-60% in the range of 0.7 sm, which is known to have improved compared to 0.7 sm (control). During the period of growth, soil mechanical composition, volume mass and granularity were positively affected in the range of 76 cm, root system and the growth and development of the porous were affected and additional 2.1 ts/ha were harvested. When the quality indicators of fiber were analyzed, the range of porous control was determined at 60 cm compared to 76 sm, copper-microneur 0.1%, Mat-ripening coefficient 0.01%, Str-comparable elongation strength 1.5 g strength/teks, UI-uniformity Index 1.4%, SFI-kalta fiber index 1.2%.